Assessment of seasonal variations of some heavy metals in water samples collected from Gwaigwaye, Maska and Zobe dams - Mustapha, Aminu; Musa, Muhammad Salisu; Salihu Chiroma, Sufyan; Nafiu , Kabir; Rawayau Zainab , Kabir (International Journal of Advanced Chemistry, 2024)
Water pollution can Damage Aquatic Ecosystems, leading to Death of Fish, plants and other Aquatic organism, which in turn can Disrupt the Entire Food chains. This study was conducted to Determine the Concentrations of Some Heavy metals in water samples obtained from Gwaigwaye, Maska and Zobe Dams in Dry and wet Seasons. The Dams provides water for Drinking, Fishing, Farming and other Agricultural Activities to the Neighbouring Communities. In this study water samples collected from Gwaigwaye, Maska and Zobe Dams in Dry and wet Seasons were Analyzed for Some Heavy metals namely, Cadmium, Cobalt, Copper, Nickel, lead and zinc. After Samples Digestion, microwave plasma atomic emission spectroscopy(MPAES) was used for the Determination of the Metal concentrations and their Levels were compared with permissible limits set by local and international standard regulatory Authorities. From the result of the Analysis, the Concentrations of the Heavy metals in Dry season in mg/L ranged as follows. 0.00±0.00 to 0.03±0.00 mg/L for Cd, 0.02±0.00 to 0.084±0.002 mg/L for Co, 0.057±0.003to 0.186±0.003 mg/L for Cu, 0.03±0.00 to 0.19±0.005 mg/L for Ni, 0.00±0.00 to 0.01±0.00 mg/L for Pb and 0.06±0.02-0.193±0.003 mg/L for Zinc. Similarly, the Concentrations of metals in wet season in(mg/L) ranged as follows, 0.00±0.00 to 0.027±0.002 for Cd, 0.02±0.002 to 0.071±0.002 for Co, 0.051±0.003 to 0.103±0.014 for Cu, 0.029±0.003 to 0.12±0.013 for Ni, 0.00±0.00 to 0.00±0.00 for pb and 0.057±0.002 to 0.160±0.003 for Zinc. The Concentrations level of Cd, Co and Ni in water samples from Maska, Gwaigwaye and Zobe Dams in dry season were above the permissible set by WHO/SON. However, Cu, Pb and Zn were within the permissible limit of WHO and SON in all the Dams in dry and wet seasons. The Result of Statistical Analysis indicated no Significant Difference between the Metals in all the Dams in both Dry and Wet seasons as p values were greater than 0.05( p >0.05).